The role of inhibitory control in task switching - Yang, Violet Hye-Won (2010)
Previous research on task switching has been confounded by inhibitory control mechanism and there has been debate on the source of switch costs and how and when the inhibitory control occurs during task switching. In order to circumvent this problem, the thesis aimed to investigate the role of inhibition in task switching by examining switch costs, alternating switch costs and congruency effect in three tasks when two preparation intervals (short and long) are given. Task switching experiments in the present study captured both flexibility (changes in task) and anticipatory control (preparation interval between cue and target) and provided the measurement for inhibitory control, 'backward inhibition' by alternating switch cost. Backward inhibition was manifest in longer reaction times (and/or more errors) to alternating switch trials (ABA) than to double switch trials (CBA). Reaction time and error in the present study also reflected whether the task in the current trials were easy when it requires the same response as the task in the previous trials, i.e., whether the required response were congruent.